1977
DOI: 10.1302/0301-620x.59b2.873978
|View full text |Cite
|
Sign up to set email alerts
|

The morphometry and pathological anatomy of the lumbar spine in South African negroes and caucasoids with specific reference to spinal stenosis

Abstract: Direct measurements were made on 2,166 lumbar vertebrae of 433 adult negro and caucasoid skeletons. On statistical analysis, forty-five vertebrae in twenty-seven skeletons were found to be stenotic, the mid-sagittal diameter being the significantly reduced dimension. Whereas spinal stenosis syndromes are rare in South African negroes, the lumbar canal is marginally narrower in the negro. There is a uniformity of configuration and capacity of the lumbar spinal canal, which transcends race and sex. By a new meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
93
0
4

Year Published

1986
1986
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(106 citation statements)
references
References 14 publications
9
93
0
4
Order By: Relevance
“…Our values for each sex are generally similar to those measured by Catalina-Herrera (1987). The lack of a significant sexual dimorphism in foramen magnum size-as found in the current study-is consistent with earlier reports showing an absence of larger male vertebral canal dimensions (Eisenstein, 1977;Porter et al, 1978;Hasue et al, 1983;Kikuchi et al, 1984). Weak sexual dimorphism is probably a result of the fact that the size of the spinal cord may be determined by the number of neural elements in the cord (Fox and Wilczynski, 1986) which in turn depends on the number of motor units in peripheral muscles and sensory nerve endings.…”
Section: Discussionsupporting
confidence: 92%
“…Our values for each sex are generally similar to those measured by Catalina-Herrera (1987). The lack of a significant sexual dimorphism in foramen magnum size-as found in the current study-is consistent with earlier reports showing an absence of larger male vertebral canal dimensions (Eisenstein, 1977;Porter et al, 1978;Hasue et al, 1983;Kikuchi et al, 1984). Weak sexual dimorphism is probably a result of the fact that the size of the spinal cord may be determined by the number of neural elements in the cord (Fox and Wilczynski, 1986) which in turn depends on the number of motor units in peripheral muscles and sensory nerve endings.…”
Section: Discussionsupporting
confidence: 92%
“…Several studies have attempted morphometrically to characterize the lumbar spine in individuals with degenerative lumbar spinal stenosis (DLSS) with diverse results [3,[14][15][16][17][18][19][20][21][22]. Some radiological studies have reported that the changes in the anterior-posterior (AP) diameter, transverse diameter and cross-section area (CSA) of the spinal canal and dural sac are risk factors for developing spinal stenosis [16,17,23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Some radiological studies have reported that the changes in the anterior-posterior (AP) diameter, transverse diameter and cross-section area (CSA) of the spinal canal and dural sac are risk factors for developing spinal stenosis [16,17,23,24]. Other studies focused on degenerative changes of the intervertebral disc, zygapophyseal joints and ligamentum flavum as dominant contributors of degenerative LSS [10-12, 25, 26].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have depended on direct measurements from plain X-ray films [9,12,13,23], or from computed tomographic (CT) scans [8,11,26,34,36]. A few reports have involved the analysis of cadaveric specimens [1,7,24,27,29]. The value of the data has depended on the number of samples and the accuracy of Abstract The precise dimensions of the lumbar vertebrae and discs are critical for the production of appropriate spinal implants.…”
mentioning
confidence: 99%